Impact of COVID-19 on the Behavioral Intention of Job Seekers Towards E-recruitment: A Post-COVID Study - Mia, Md. Abdul Hannan; Rob, Rukaiya (Bangladesh Journal of MIS, 2025)
Restrictions on face-to-face social interactions due to COVID-19 made traditional recruitment limited, pushing both employers and job seekers to rely on e-recruitment. This shift highlights the importance of understanding the willingness of job seekers to adopt this technology. The purpose of this paper is to examine the impact of COVID-19 on job seekers’ behavioral intention toward e-recruitment. A modified Technology Acceptance Model (TAM) was used for the purpose of the study. Behavioral intention of the job seekers was thought to be affected by Perceived Ease of Use (PEU), Perceived Usefulness (PU), Subjective Norms (SN), and COVID-19. 441 job seekers were surveyed using a structured questionnaire developed around the model’s premise. The collected data were analyzed using structural equation modelling (SEM). The study identified a positive relationship between the dependent and independent variables. COVID-19 was found to have a significant direct impact on the behavioral intention of job seekers toward e-recruitment. The study findings imply that recruiters must consider COVID-19 when designing their online recruitment process. This paper offers guidance for HR professionals, businesses, e-recruitment service providers, and job portals regarding the strategy for designing their online recruitment process, platforms, or websites to attract a large pool of job seekers. This study contributes to the existing literature on job seekers’ intentions to use e-recruitment technology in developing countries.